The Impact of (Opportunity and Necessity) Entrepreneurship on Economic Growth: Does Human Capital Matter? - Daniela Ribeiro Rodrigues (2018)
Entrepreneurship is generally defined as the creation of new firms and according to literature, it is the process by which new enterprises are founded and become viable. Although considerable research has been devoted to the study of the impact of entrepreneurship on economic growth, fewer studies have analyzed the impact of the types (opportunity vs necessity) of entrepreneurship on economic growth. Moreover, the latter set of studies overlooked the relevance of human capital as mediating factor in the relation between (types of) entrepreneurship and economic growth. The aim of the present study was to fill in the above mentioned gap, by assessing the extent to which the direct and indirect impact of (the types of) entrepreneurship, via human capital, matters for countries' economic growth. In methodological terms, we resort to fixed effects panel data estimations, involving a large set of (OECD and non-OECD) countries, over a relatively long time span (1990-2016). The results suggest that total entrepreneurship have a positive impact on economic growth. Distinguishing between types of entrepreneurship, there is clear evidence that opportunity entrepreneurship fosters economic growth, whereas necessity entrepreneurship inhibits it. Interestingtly, human capital tends to mitigate the negative impact of necessity entrepreneurship on economic growth. In the case of opportunity entrepreneurship, the direct positive impact observed is reduced in contexts characterized by high levels of human capital, which might reflect increased opportunity costs.